Exposure to methylmercury chloride inhibits mitochondrial electron transport chain and phosphotransfer network in liver and gills of grass carp: Protective effects of diphenyl diselenide dietary supplementation as an alternative strategy for mercury toxicity - Baldissera M.D. (2019)
© 2019 Elsevier B.V.Methylmercury chloride (CH3HgCl) is an important contaminant found in the environment that exerts highly toxic effects in multiple organs of aquatic animals. Recently, some studies revealed the toxic effects of methylmercury and mercury chloride to the energetic metabolism of rodents. However, possible toxic effects of CH3HgCl related to bioenergetic homeostasis of adenosine triphosphate (ATP) in aquatic animals, such as fish, remain unknown. Moreover, recent evidence has demonstrated the protective effects of diphenyl diselenide (Ph2Se2) in a model of fish poisoning by mercury chloride, but its possible protective effects on bioenergetic homeostasis are not yet established. Thus, the aim of this study was to evaluate whether a dietary supplementation with Ph2Se2 prevents or minimizes hepatic and branchial bioenergetic dysfunction elicited by CH3HgCl via protective effects on respiratory chain complexes and phosphotransfer network pathway. Branchial cytosolic and mitochondrial creatine kinase activity and hepatic and branchial mitochondrial complexes II, II-III and IV activities were inhibited (except for mitochondrial complex IV in gills) in fish exposed to CH3HgCl when compared to control group. Moreover, the hepatic and branchial ATP content, as well as sodium-potassium pump (Na+/K+-ATPase) and proton-pump (H+-ATPase) activities were inhibited in fish exposed to CH3HgCl when compared to control group. Finally, a significant increase on reactive oxygen species levels was observed in fish exposed to CH3HgCl in comparison to control group, while non-protein thiols and protein thiols groups were decreased. Dietary supplementation with 3 mg/kg Ph2Se2 prevented or reduced all alterations elicited by CH3HgCl. In summary, Ph2Se2 can be considered a suitable approach to prevent/minimize the hepatic and branchial bioenergetic dysfunction elicited by CH3HgCl.